A rare case of hydatid cyst of the interventricular septum - Patel, Monila; Khan, Rafe; Dave, Ruchir; Vora, Jyoti; Shah, Sneha; Singhvi, Shreyans D.; Singh, Preksha T. (International Journal of Research in Medical Sciences, 2020)
A Hydatid disease or Echinococcosis is a zoonotic disease caused by the larvae (metacestode) of the cestode species of the genus Echinococcus. Humans are the accidental hosts of the diseases; they usually acquire it from canines; which are the definite host. It can present with systemic cyst, while cardiac manifestation of the disease is rare, due to contractile property of the heart’s muscle fiber which provide resistance. In this case report, the patient is diagnosed with hydatid cyst in the inter ventricular septum; it’s diagnosis and its successful treatment with surgery and albendazole. As, inter ventricular septum hydatid cyst occurs in only 0.5-2% cases, it’s a unique case and its successful treatment and diagnosis can help the physicians in the future to treat a similar case as this.